PENGEMBANGAN FUNGSI HUNIAN BERDASARKAN IDENTITAS LOKAL PADA AREA WATERFRONT DI PASAR LAMA TANGERANG - Louis Osvaldo Xavier; Felia Srinaga; Alvar Mensana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2018)
Title: The Development of Residential District based on Local Identity on Waterfront Area at Pasar Lama Tangerang The waterfront edges along Cisadane river considered as one of the environmental assets in the area of Pasar Lama (Old Town Market) in the city of Tangerang. However, such valuable asset is neglected due to current urban planning issues specifically on the placement of residential district and land-use planning within Pasar Lama adjacent context. This might caused disintegration between the residential and the commercial areas as the objective of a city to create a sense of place– it’s also diminished the identity of Pasar Lama (Old Town Market) as a Chinatown on the banks of the Cisadane River. This research study aim to raise several questions, namely: what are the criteria for a proper residential neighborhood in the context of the waterfront area, what is the function of residential district that has its own particular identity and how does it suitable for the particular context of waterfront area in Pasar Lama (Old Town Market), and how does the concept of identity could be applied on the waterfront area, in the Tangerang’s Pasar Lama (Old Town Market). This research study based on data collected from literature studies, field observations and on-site interview. The literature study discuss the functions of identity for a residential district, waterfront area and Pasar Lama (Old Town Market). Field observation studies were carried out to examine the theory and analyze the function of residential neighborhood, building accessibility, supporting facilities for residential areas, and Pasar Lama (Old Town Market) identity. The results of this study are finding the residential functions in which aligned with the parameters on residential design in the waterfront area and the local identity of the Tangerang Pasar Lama (Old Town Market). It aims to make the Pasar Lama (Old Town Market) areas to create and establish the local identity reflecting tourism, commercial and residential neighborhood, in addition to the mixed-use development on the waterfront area around the banks of the Cisadane river. Lastly, this research study also attempt to re-configure the land- use planning as well as strategize on how to locate the residential district that supports the relationship to its adjacent commercial areas.